Comparative SARS-CoV-2 Omicron BA.5 variant and D614G-Wuhan strain infections in ferrets: insights into attenuation and disease progression during subclinical to mild COVID-19 - Barroso-Arévalo, Sandra; Sánchez-Morales, Lidia; Porras, Néstor; Díaz-Frutos, Marta; Barasona, Jose A.; Isla, Julio; López, Débora; Gortázar, Christian; Domínguez, Lucas; Sánchez-Vizcaíno, Jose M. (Frontiers in Veterinary Science, 2024)
Given the continuous evolution of the SARS-CoV-2 virus and the emergence of new variants, understanding the comparative pathological and immunological outcomes of different strains is of paramount importance. Specifically, SARS-CoV-2 infections caused by the original Wuhan strain and the Omicron variant have shown significant disparities in clinical behavior and immunological response, as demonstrated in numerous field and experimental studies. Here, we evaluate the D614G variant (derived from the Wuhan strain) and Omicron BA.5 variant using ferrets as experimental model. Both strains were inoculated into a group of ferrets, with greater disease severity and viral dissemination being observed in those infected with the D614G strain. Furthermore, a robust neutralizing antibody response was markedly evident in ferrets infected with the D614G-Wuhan strain, whereas ferrets infected with Omicron variant did not generate a detectable neutralizing antibody response. Despite viral clearance from nearly all tissues by 7 days post-infection (dpi), an increase in pathological lesions was observed between 14 and 21 dpi, particularly in the D614G-Wuhan-infected group, indicating a sustained immune response even after viral clearance. The results from this investigation underscore the adaptability of SARS-CoV-2, shedding light on variations in susceptibility and clinical manifestations across different species and strains of the virus. These findings also emphasize the importance of considering both the direct effects of viral infection and the indirect, often longer-term, effects of the immune response when evaluating the outcomes of SARS-CoV-2 infection.